“But I’m Also from There”: Transnational Adoption, Belonging and Cultural Identity in Susi Gonzalvo’s Zhao - Sheldon, Megan (Revista Canadiense de Estudios Hispánicos, 2023)
This paper examines Susi Gonzalvo’s Zhao (2008) within the context of increasing international adoption during the 1990s and the start of the new millennium, specifically in Spain. Taking into account the film’s use of a non-linear narrative, flashback sequences and textual media, this article argues that the film represents the struggle experienced by transnational adoptees to resolve their feelings of belonging and non-belonging as they navigate a complex cultural terrain. The article also contrasts the representation of the protagonist in Gonzalvo’s film with the representation of young Chinese adopted girls in David Gózman Rollán’s documentary Generación Mei Ming (2014).